Searching for long-lived dark scalars at the FCC-ee - G. Ripellino; M. Vande Voorde; A. Gallén; R. Gonzalez Suarez (Journal of High Energy Physics)
Abstract This paper investigates the search for long-lived dark scalars from exotic Higgs boson decays at the Future Circular Collider in its e + e − stage, FCC-ee, considering an integrated luminosity of 10.8 ab−1 collected during the ZH run at a center-of-mass energy s $$ \sqrt{s} $$ = 240 GeV. The work considers Zh events where the Z boson decays leptonically and the Higgs boson h decays into two long-lived dark scalars s which further decay into bottom anti-bottom quark pairs. The analysis is performed using a parametrized simulation of the IDEA detector concept and targets dark scalar decays in the tracking volume, resulting in multiple displaced vertices in the final state. The sensitivity towards long-lived dark scalars at FCC-ee is estimated using an event selection requiring two opposite-charge, same-flavor leptons compatible with the Z boson, and at least two displaced vertices in the final state. The selection is seen to efficiently remove the Standard Model background, while retaining sensitivity for dark scalar masses between m s = 20 GeV and m s = 60 GeV and mean proper lifetimes cτ between approximately 10 mm and 10 m. The results show that the search strategy has potential to probe Higgs to dark scalar branching ratios as low as 10−4 for a mean proper lifetime cτ ≈ 1 m. The results provide the first sensitivity estimate for exotic Higgs decays at FCC-ee with the IDEA detector concept, using the common FCC framework.